Dietary inflammatory potential is associated with sarcopenia in patients with hypertension: national health and nutrition examination study - Tu, Jiabin; Shi, Shanshan; Liu, Yuchen; Xiu, Jiaming; Zhang, Yanbin; Wu, Bo; Liao, Ying; Chen, Kaihong; Li, Ganyang; Chen, Llling (Frontiers in Nutrition, 2023)
Abstract: Background: Study has shown that sarcopenia increases the risk of poor outcomes in patients with hypertension. Inflammation is one of the important reasons for the occurrence and development of sarcopenia. Regulating systemic inflammation may be a potential intervention for sarcopenia in hypertensive patients. Diet is one of the important measures to improve systemic inflammation. The dietary inflammatory index (DII) is a tool designed to assess the inflammatory potential of the diet, the association between DII and sarcopenia in hypertensive patients is unclear. Objective: To explore the relationship between the DII and sarcopenia in patients with hypertension. Method: Data from the National Health and Nutrition Examination Survey (NHANES) 1999–2006 and 2011-2018. A total of 7,829 participants were evaluated. Participants were divided into four groups based on the quartile of the DII: Q1 group (n=1,958), Q2 group (n=1,956), Q3 group (n=1,958) and Q4 group (n=1,957). The relationship between the DII and sarcopenia was assessed by logistic regression analysis based on the NHANES recommended weights. Result: The DII was significantly associated with sarcopenia in patients with hypertension. After full adjustment, patients with higher DII (OR: 1.22, 95% CI: 1.13 -1.32, P<0.001) have a higher risk of sarcopenia. Compared with Q1 group, the group with higher DII levels had a higher risk of sarcopenia (Q2: OR: 1.23, 95%CI: 0.89-1.72, P=0.209; Q3: OR: 1.68, 95%CI: 1.20-2.35, P=0.003; Q4: OR: 2.43, 95%CI: 1.74-3.39, P<0.001). Conclusion: High DII is associated with an increased risk of sarcopenia in hypertensive patients. The higher the DII, the higher the risk of sarcopenia in hypertensive patients.